Penerapan Srtategi Pembelajaran Think Talk Write (Ttw) Bermedia Gambar Untuk Meningkatkan Aktivitas Belajar Dan Keterampilan Menulis Puisi Siswa - I Wayan Kerti (Cetta: Jurnal Ilmu Pendidikan, 2018)
This study aims to improve; learning activities and skills to write poetry students of class VII-B SMP Negeri 5 Abang semester 2 year lesson 2016/2017. This study used a classroom action research design through two cycles. Student learning activity data is collected by observation sheet, and data of student poetry writing skill is collected by test method which is analyzed by quantitative descriptive method. Before the second cycle is done, firstly done rekavitulasi data writing creative value of class VII students three years previous lessons, and asked the previous teacher of Indonesian language about student learning activities combined with the results of observations of teachers of researchers on previous learning. This data is used as initial data of learning activity and skill of writing poetry of class VII student at SMP Negeri 5 Abang. The result of the research shows that the implementation of talk-writing write (TTW) strategy with the help of picture media can increase the learning activity and poetry writing skill of VII-B students of SMP Negeri 5 Abang 2nd semester of academic year 2016/2017, that is the average of student learning activity on cycle I was 70 (positive enough category) with 52% classical completeness, while in cycle II the average of student learning activity was 80 (positive category) with 89% classical completeness. The average student's poetry writing skills also increased significantly from the average of 72, 72% absorption, 63% classical completeness in cycle I, the average score of students' writing poetry skills is 75, absorbency 75%, and mastery classical 89% in cycle II.